Biology‐Oriented Synthesis of a Tetrahydroisoquinoline‐Based Compound Collection Targeting Microtubule Polymerization. Issue 3 (31st January 2013) - Zimmermann, Tobias J.; Roy, Sayantani; Martinez, Nancy E.; Ziegler, Slava; Hedberg, Christian; Waldmann, Herbert
<x xml:space="preserve">Abstract</x> In the third place: Inspired by the tetrahydroisoquinoline (THIQ) alkaloid noscapine, inhibitors of tubulin polymerization that bind to a site different from the colchicine and the vinca alkaloid binding sites have been synthesized. One compound is more potent than noscapine in HeLa cells and can overcome resistance to chemotherapeutics.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>